Analysis of Students' Design Thinking in Information Technology Innovation - Indriaturrahmi, Indriaturrahmi; Prayogi, Saiful; Asy'ari, Muhammad; Samsuri, Taufik (Lensa: Jurnal Kependidikan Fisika, 2023)
This study delves into the design thinking characteristics among students in the field of information technology innovation, examining their competencies within the context of the Information Technology Education program at Mandalika University of Education - Indonesia. Employing an exploratory descriptive research design, the research focuses on 30 students, utilizing the Design Thinking Scale to assess six crucial dimensions: comfort with uncertainty and risks, human-centeredness, mindfulness of the process and impacts on others, collaborative work with diversity, orientation to learning by making and testing, and confidence and optimism to use creativity. The findings reveal a comprehensive understanding of the nuanced aspects of students' design thinking capabilities, indicating areas for improvement. Notably, students exhibit discomfort with uncertainty and risks, signaling a need for interventions to enhance resilience and adaptability. Human-centeredness, collaborative work with diversity, and mindfulness to the process receive "Poor" and "Fair" ratings, emphasizing the importance of fostering user-centric approaches and enhancing collaborative competencies. While students demonstrate a moderate level of competency in practical learning and creative application, there is room for improvement in orientation to learning by making and testing and confidence and optimism to use creativity. The overall "Poor" rating for the average design thinking score suggests a collective need for targeted interventions and educational strategies. This study contributes to the ongoing discourse on design thinking in IT education. It offers insights that can inform tailored pedagogical approaches and interventions to enhance students' design thinking capabilities in preparation for the dynamic challenges of the evolving information technology landscape.